Comparative study of methanolic and aqueous extracts of Cocculus hirsutus leaves on specific and non specific immune responses - Arunabha Mallik; Satish Nayak (International Journal of Phytomedicine, 2014)
The aim of the present study was to find out comparatively about methanolic and aqueous extract of Cocculus hirsutus on specific and non specific immune responses in experimental mice. Oral administration of the methanolic (200 and 400 mg/kg) and aqueous extract (250 and 500 mg/kg) were studied on various immune paradigm like determination of antibody titer, delayed type hypersensitivity reaction using SRBC as an antigen, carbon clearance assay as a measure of phagocytic index and total leukocyte count in cyclophosphamide induce immunosuppresed animals. Methanolic extract of Cocculus hirsutus to a large extent enhanced specific and non-specific activity in dose 200 and 400 mg/kg body weight. Aqueous extract at 250 mg/kg dose level failed to show appreciably immunomodulatory activity but 500 mg/kg of aqueous extract potentiated the activity however less significantly compared with both dose of methanolic extract.